KEPEMIMPINAN PROFETIK DI LEMBAGA PENDIDIKAN PONDOK PESANTREN: Studi Kepemimpinan Profetik K.H. Adib Amrullah di Pondok Pesantren Darussa’adah, Bulus-Kritig, Petanahan, Kebumen - Muhtadi, Farid (CV. Amerta Media, 2018)
Kiai is seen as a very influential figure in pesantren life. In addition to the charismatic figure, whatever is taught by a kiai is seen as an absolute truth that can not be